Diabetes-Related Cognitive Decline, a Global Health Issue, and New Treatments Approaches - Novak, Vera (Int J Priv Health Inf Manag, 2017)
The epidemic of type 2 diabetes (T2DM) is spreading around the globe and challenging the unprecedented success of health sciences in increasing longevity. T2DM has been linked to accelerated brain aging, functional decline in older adults and dementia. Brain insulin resistance and glycemic variability are potential mechanisms underlying T2DM-related brain damage and cognitive decline. Intranasal insulin therapy has emerged as a potential new treatment for T2DM-related cognitive impairment. Wearable technologies now allow better monitoring of behaviors and glycemic levels over several days and deliver real time feedback that can be used to improve self-management and lead to new prevention strategies and therapies for T2DM complications.